2013
DOI: 10.1261/rna.041665.113
|View full text |Cite
|
Sign up to set email alerts
|

Bicaudal-C spatially controls translation of vertebrate maternal mRNAs

Abstract: The Xenopus Cripto-1 protein is confined to the cells of the animal hemisphere during early embryogenesis where it regulates the formation of anterior structures. Cripto-1 protein accumulates only in animal cells because cripto-1 mRNA in cells of the vegetal hemisphere is translationally repressed. Here, we show that the RNA binding protein, Bicaudal-C (Bic-C), functioned directly in this vegetal cell-specific repression. While Bic-C protein is normally confined to vegetal cells, ectopic expression of Bic-C in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
75
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(79 citation statements)
references
References 48 publications
4
75
0
Order By: Relevance
“…The reporter mRNA containing the wnt11b 3′UTR was repressed by co-expression of HA-Bicc1 to the same extent as the reporter containing the cripto1 3′UTR that we previously identified and characterized as a Bicc1-regulated mRNA (Fig. 3C) (Zhang et al, 2009(Zhang et al, , 2013. The effect was specific, as a reporter mRNA containing the 3′UTR from the cyclin B1 (ccnb1) mRNA, an mRNA not regulated by Bicc1, was not repressed.…”
Section: Resultsmentioning
confidence: 67%
See 4 more Smart Citations
“…The reporter mRNA containing the wnt11b 3′UTR was repressed by co-expression of HA-Bicc1 to the same extent as the reporter containing the cripto1 3′UTR that we previously identified and characterized as a Bicc1-regulated mRNA (Fig. 3C) (Zhang et al, 2009(Zhang et al, , 2013. The effect was specific, as a reporter mRNA containing the 3′UTR from the cyclin B1 (ccnb1) mRNA, an mRNA not regulated by Bicc1, was not repressed.…”
Section: Resultsmentioning
confidence: 67%
“…This phenotype showed similarity to that described for embryos that overexpress the Wnt11b ligand (Tao et al, 2005), raising the possibility that wnt11b mRNA was a direct or indirect target of Bicc1 translational repression. Although wnt11b mRNA was not identified as a Bicc1 target in our previous studies using an ectopically expressed HA-Bicc1 immunoprecipitation strategy that identified several mRNAs relevant to cell-fate decisions, there were several possible technical reasons that could cause relevant direct targets to be missed (Zhang et al, 2013). Therefore, we tested whether wnt11b mRNA encoded elements sufficient to allow Bicc1-mediated repression using a luciferase reporter mRNA assay described in our previous work (Zhang et al, 2013).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations